2014
DOI: 10.1111/jam.12424
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the mechanisms underlying the high acetylene-reducing activity exhibited by the soil bacterial community from BC2 horizon in the permafrost zone of the East Siberian larch forest bed

Abstract: Aims: This study addressed a microbial composition of East Siberian larch forest bed soil and focused on major nitrogen-fixing bacterial consortia showing the highest capacity to induce acetylene reduction. Methods and Results: The ability of a soil microbial consortium to effectively reduce acetylene was investigated using gellan gum medium. In parallel, each microbial component in the medium was analysed by a 16S rRNA genetargeting denaturing gradient gel electrophoresis (DGGE), together with an attempt to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Our reconstruction of the Janthinobacterium P10 MAG demonstrated that this genome contains a complete nif gene cluster. A related Janthinobacterium lividum V30-G6 isolated from permafrost showed low levels of N fixation via the acetylene reduction assay [74]. Bradyrhizobium spp.…”
Section: Discussionmentioning
confidence: 99%
“…Our reconstruction of the Janthinobacterium P10 MAG demonstrated that this genome contains a complete nif gene cluster. A related Janthinobacterium lividum V30-G6 isolated from permafrost showed low levels of N fixation via the acetylene reduction assay [74]. Bradyrhizobium spp.…”
Section: Discussionmentioning
confidence: 99%